2023
DOI: 10.3390/insects14040347
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Analysis of Silkworm Midgut Reveals Differences between the Physiological Effects of an Artificial and Mulberry Leaf Diet

Abstract: Bombyx mori is a model lepidopteran insect of great economic value. Mulberry leaves are its only natural food source. The development of artificial diets can not only resolve the seasonal shortage of mulberry leaves but also enable changes to be made to the feed composition according to need. Metabolomic differences between the midguts of male and female silkworms fed either on fresh mulberry leaves or an artificial diet were studied using liquid chromatography–mass spectrography (LC-MS/MS) analysis. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…The enhanced species richness observed in the SL group could be attributed to the multitude of components integrated into the artificial diet, including soybean meal, corn powder, and an assortment of nutritional additives. These components collectively foster a more diverse microbial community [5,6,12,16]. However, it is crucial to recognize that a higher microbial diversity does not automatically equate to superior host performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced species richness observed in the SL group could be attributed to the multitude of components integrated into the artificial diet, including soybean meal, corn powder, and an assortment of nutritional additives. These components collectively foster a more diverse microbial community [5,6,12,16]. However, it is crucial to recognize that a higher microbial diversity does not automatically equate to superior host performance.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient composition of mulberry leaves, particularly the balance of proteins, carbohydrates, and essential micronutrients, plays a pivotal role in the growth, development, and silk production of silkworms [4,8,9]. However, the increasing demand for silk and the need for cost-effective and efficient production methods have led to the widespread adoption of artificial diets in commercial sericulture [6,[10][11][12]. These formulated feeds, often based on a combination of soybean meal, corn powder, and various nutritional supplements, aim to provide a balanced and easily digestible nutrient profile for optimal silkworm growth [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For silkworms, MLs are considered the most suitable diet, whereas AD is a nutritionally imbalanced diet [16,36]. Studies have shown that the dietary pattern of MLs shapes the formation of similar and stable gut microbiota among individual silkworms and is crucial for their health [28].…”
Section: Dietary Transition Reshapes the Gut Microbiota Of Silkwormsmentioning
confidence: 99%
“…In order to improve production efficiency, modern sericulture has gradually started using artificial diets (ADs) as a substitute for MLs in silkworm rearing [15]. However, silkworms fed on ADs exhibit significantly diminished robustness and silk production efficiency [16,17]. Studies using mice and other models have revealed that a high-fat diet (HFD) or high-sugar diet (HSD) significantly affects the composition and function of the gut microbiota, thus impairing the host's metabolic homeostasis [18,19].…”
Section: Introductionmentioning
confidence: 99%